Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.20517/2574-1209.2018.44
|View full text |Cite
|
Sign up to set email alerts
|

A current view of G protein-coupled receptor - mediated signaling in pulmonary hypertension: finding opportunities for therapeutic intervention

Abstract: Pathological vascular remodeling is observed in various cardiovascular diseases including pulmonary hypertension (PH), a disease of unknown etiology that has been characterized by pulmonary artery vasoconstriction, right ventricular hypertrophy, vascular inflammation, and abnormal angiogenesis in pulmonary circulation. G protein-coupled receptors (GPCRs) are the largest family in the genome and widely expressed in cardiovascular system. They regulate all aspects of PH pathophysiology and represent therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 252 publications
1
12
0
1
Order By: Relevance
“…These two processes do interact [45], but it remains uncertain regarding the true primary driver in this interaction. Indeed, changes in cholesterol metabolism can affect inflammatory responses of macrophages [37][38][39][40]43,[46][47][48]. However, we recently revealed ten genes that may be the key regulators of foam cell formation [25].…”
Section: Discussionmentioning
confidence: 99%
“…These two processes do interact [45], but it remains uncertain regarding the true primary driver in this interaction. Indeed, changes in cholesterol metabolism can affect inflammatory responses of macrophages [37][38][39][40]43,[46][47][48]. However, we recently revealed ten genes that may be the key regulators of foam cell formation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that the development of certain autoimmune diseases was associated with a decrease in the overall level of IgG sialylation. In the cases of individual nosologies, a relationship has been found between total IgG or IgG autoantibodies decreased sialylation and the pathological activity of autoantibodies [37], and with severity of disease symptoms [38], its activity and course [39,40], and the response to treatment [41,42].…”
Section: Glycosylation Of Immunoglobulins: the Effects In Various Dismentioning
confidence: 99%
“…Thanks to these results, inflammation regained the attention as possible point of therapeutic intervention for atherosclerosis treatment. However, it appeared to be more promising to target specific proinflammatory pathways rather than inflammation in general [12][13][14].…”
Section: Introductionmentioning
confidence: 99%